2017
DOI: 10.4103/ccd.ccd_165_17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of salivary cortisol changes and psychological profiles in patients with recurrent aphthous stomatitis

Abstract: Background and Objective:Some studies suggest that psychological condition and stress can play role in the development of recurrent aphthous stomatitis (RAS). The purpose of this study was to evaluate salivary cortisol changes and psychological conditions in patients with RAS.Materials and Methods:Twenty-seven patients (13 males and 14 females, mean age of 32.8 (±10.2) years) with minor RAS and 27 age- and sex-matched controls without RAS participated in this study. The concentration of cortisol (nanomole/L) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…In this study, more than half of the respondents were anxious, 58.2%. This nding is consistent with papers published locally and abroad [17][18][19][20][21][22][23][24] . The highest rates of anxiety disorder among patients with RAS was reported by Ajmal et.al.…”
Section: Anxiety Associated With Rassupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, more than half of the respondents were anxious, 58.2%. This nding is consistent with papers published locally and abroad [17][18][19][20][21][22][23][24] . The highest rates of anxiety disorder among patients with RAS was reported by Ajmal et.al.…”
Section: Anxiety Associated With Rassupporting
confidence: 92%
“…Articles on the same subject have discussed stressful events in various forms. [21][22][23][24][25][26][27][28] The highest incidence of stress among patients with RAS was recorded by Ajmal et.al. 16 They reported that 90% of patients with RAS were exposed to stress.…”
Section: Stress Associated With Rasmentioning
confidence: 99%
“…In fact, RAS is a cellular immune response in which T lymphocytes, cytokines, and tumor necrosis cause epithelial cell death and ulcer. [1213] Natural healing of ulcers and oral lesions is the result of a complex interaction among various types of cells at the ulcer area and their ability in producing a series of growth factors and responses. These factors regulate growth, cell migration and proliferation, extracellular matrix production, enzymatic activity, and higher growth factor production.…”
Section: Discussionmentioning
confidence: 99%
“…Prema novijim studijima psihološki stres djeluje kao trigger ili modificirajući čimbenik za razvoj lezija kod pacijenata sklonim RAS-u 11,20,21 . U prilog tome govore i povećane razine salivarnog kortizola kod oboljelih 20,22,23 , iako novije studije navode da se stres, anksioznost i depresija mogu povezati s pojavom RAS-a bez značajne promjene nivoa kortizola 24,25 . S druge strane, neka istraživanja, uspoređujući stupanj psihološkog stresa u akutnoj fazi i fazi remisije RAS-a, zaključuju da nema povezanosti između psihološ-kog stresa i RAS-a 26,27 .…”
Section: Stresunclassified